Análise do conforto de aplicadores para terapia estética sob a ótica da ergonomia - Shimizu, Ari Koji [UNESP] (2015)
The increase demand for aesthetic therapy, caused by the search of beauty standards defined by the media and by society, especially by females has led the aesthetic therapists to an overload of work. In the survey conducted in this study with those professionals in this area, it was proved that they are at hhigh risk of contracting musculoskeletal disorders of the upper limbs resulting from repetitive movements, equipment vibration, static muscular load, mechanical stress, and extreme positions taken in handling some equipment that somethimes are not designed properly under the ergonomic point of view. Given this situation, this research aims to contribute to reducing these musculoskeletal injuries to therapists caused by the use of equipment by developing an applicator's handle for aesthetic therapy with emphasis on ergonomics, that is was performed in three stages: pre-design development ans post-design. In the pre-design stage, interviews and questionnaires were conducted with therapists using aesthetic equipment in order to know the user's profile, collect data on the use of equipment and also with a goal to contributing to the development of the product. In the development phase, a project methodology was adopted that in the macro-structural level, emncompasses concepts to the creation and troubleshooting, starting with a pre-existing need. After the development of the product, ie, the post-design stage, the use of applicator's handles simulations were performed to read the palm forces and subjective perception with volunteers, using gloves equipped with FSR (Force Sensor Resistor) sensors. It became clear the improvement in the applicator's handle model developed through the interpretation of the simulation results and based on authors who were part of the literature review. Thus, it is concluded that the main objective was achieved, given that the design of the cable aesthetic therapy applicators brought about an effective result in...